PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KURSUS ONLINE (Pada PT Kemitraan Kuliner Indonesia) - C Chusnah; S Sunarno; Hamzah Fansuri Nambi (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2023)
The purpose of this study was to determine the effect of price and product quality on the purchasing decision to take an online course at PT Kemitraan Kuliner Indonesia. The population in this study are consumers who’s been buying the frozen food secret recipe online course in the last 2 years at PT Kemitraan Kuliner Indonesia. The sample in this study consisted of 100 respondents. The analysis methods used in this study are validity test and reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis and multiple correlation analysis, determination analysis, f test and t test using the SPSS 25 program. Based on the results of the price variable t test research can a concluded that price has a positive and significant effect on the purchasing decision to take the course. Product quality variable t test can be concluded that Product Quality has a positive and significant effect on the purchasing decision to take an online course at PT Kemitraan Kuliner Indonesia. Based on the results of the coefficient of determination (R2) of 0.859, it shows that the Price and Product Quality variables are able to partially explain 85.9% of the variation that occurs in Purchasing Decisions, while 14.1% is another factor.